PENGARUH GAME-BASED LEARNING 'BLOOKET' TERHADAP PENINGKATAN KETERAMPILAN PROBLEM SOLVING SISWA KELAS XI INFORMATIKA MATERI TOPOLOGI DAN KEAMANAN JARINGAN DI SMAK TUNAS GLORIA - T. Derosari, Katarina; J. Taku Neno, Katrin; Enstein, Jhon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the cognitive challenges and passive learning conditions faced by eleventh-grade students at SMAK Tunas Gloria Kupang in understanding abstract Informatics concepts, specifically Network Topology and Security. The research aims to analyze the significant impact of integrating the game-based learning platform Blooket, assisted by the Cisco Packet Tracer simulator, on improving students' problem-solving skills based on George Polya's four-stage framework. Utilizing a quantitative method with a pre-experimental one-group pretest-posttest design, the study involved a purposive sample of 14 students from class XI-A. Data collection methods included essay tests evaluated via a graded rubric, classroom observations, and documentation, which were statistically processed using IBM SPSS Statistics 31. The results of the Shapiro-Wilk normality test (p > 0.05) and Levene's homogeneity test (p = 0.310) met the requirements for parametric analysis. The Paired Samples T-Test revealed a highly significant difference between the pretest and posttest scores with a significance value of p < 0.001 and a t-statistic of -6.124. This statistical outcome conclusively rejects the null hypothesis (H0). Empirically, the students' mean score increased substantially from 57.29 in the pretest to 84.82 in the posttest. Furthermore, the Normalized Gain (N-Gain) analysis yielded an average score of 0.6442 (64.42%), placing the overall effectiveness of this digital learning intervention in the "Medium" category. Observation data corroborated these findings, indicating elevated cognitive focus and intrinsic motivation. In conclusion, the strategic combination of Blooket and Cisco Packet Tracer is highly effective in transforming conventional instruction into an interactive, student-centered ecosystem that successfully fosters robust digital troubleshooting capabilities.